Experimentally validated hopping-transport model for energetically disordered organic semiconductors - Upreti, Tanvi; Wang, Yuming; Zhang, Huotian; Scheunemann, Dorothea; Gao, Feng; Kemerink, Martijn (Physical review applied, 2019)
Charge transport in disordered organic semiconductors occurs by hopping of charge carriers between localized sites that are randomly distributed in a strongly energy-dependent density of states. Extracting disorder and hopping parameters from experimental data, such as temperature-dependent current-voltage characteristics, typically relies on parametrized mobility functionals that are integrated in a drift-diffusion solver. Surprisingly, the functional based on the extended Gaussian disorder model (eGDM) is extremely successful at this, despite it being based on the assumption of nearest neighbor hopping (nnH) on a regular lattice. We here propose a variable-range hopping (VRH) model that is integrated in a freeware drift-diffusion solver. The mobility model is calibrated using kinetic Monte Carlo calculations and shows good agreement with the Monte Carlo calculations over the experimentally relevant part of the parameter space. The model is applied to temperature-dependent space-charge-limited current (SCLC) measurements of different systems. In contrast to the eGDM, the VRH model provides a consistent description of both p- and n-type devices. We find a critical ratio of aNN/α (mean intersite distance:localization radius) of about three, below which hopping to non-nearest neighbors becomes important around room temperature and the eGDM cannot be used for parameter extraction. Typical (Gaussian) disorder values in the range 45-120 meV are found, without any clear correlation with photovoltaic performance, when the same active layer is used in an organic solar cell.